Denatured protein stabilized drug nanoparticles: tunable drug state and penetration across the intestinal barrier. Issue 5 (19th January 2017) - He, Wei; Wang, Yiao; Lv, Yaqi; Xiao, Qingqing; Ye, Ling; Cai, Bo; Qin, Chao; Han, Xiaopeng; Cai, Ting; Yin, Lifang
Abstract : A novel denatured protein-coated nanosuspension the drug state of which was tunable and could penetrate across the intestinal barrier was reported. Abstract : Nanosuspensions of drugs are nanosized colloidal dispersions of pure particles. In contrast to conventional nanoparticles, the particles in nanosuspensions feature 100% drug loading. Stiripentol (STP) is an effective drug for severe myoclonic epilepsy of infancy (SMEI); however, because of its low water solubility, high oral doses of STP, up to 50 mg per kg per day in two or three divided doses, must be administered to patients, compromising therapy outcomes. Here, we report STP nanosuspensions (STP-Ns) stabilized with denatured soybean protein isolate (SPI) as a stabilizer to promote the absorption of STP and thus improve therapeutic outcomes. STP-Ns with a drug loading of up to 50% (w/w) and a diameter of 150 nm were successfully prepared. Importantly, in the presence of denatured SPI as a stabilizer, the drug state in the nanosuspensions was tunable by drug loading: low drug loading resulted in the formation of amorphous drug nanoparticles while high drug loading greater than 3.22% (w/w) in formulation induced the formation of nanosuspensions with the coexistence of amorphous and crystalline drug. This new nanosuspension formulation was related to the fact that the protein–drug complex exhibited a much stronger affinity for the drug particles over the protein itself. Interestingly, via the transcytosis pathway, the STP-Ns penetrated across the intestinal barrier into the systemic circulation, with the duodenum as the predominant absorption site. The bioavailability of the STP-Ns was 4-fold as great as that of raw crystals. The discovery of this mechanism for the use of globular protein as a stabilizer for nanosuspensions provides a new route for the preparation of amorphous drug nanoparticles. This work offers a new strategy to widen the application of globular protein and nanosuspensions of insoluble active compounds in drug delivery.